The Blue Economy in the Arctic Ocean: Governing Aquaculture in Alaska and North Norway - Andreas RASPOTNIK; Svein V. ROTTEM; Andreas ØSTHAGEN (Arctic and North, 2021)
In the Arctic, the concept of the blue economy is increasingly dominating discussions on regional development. This entails utilising the region’s ocean-based resources in a sustainable way — both from a global and local level, as well as from an environmental and economic perspective. A crucial aspect in this development is how blue activities are regulated. The UNCLOS-regime plays a vital part in providing the mechanisms and procedures for states to manage marine resources more broadly. However, the predominant mode of governance for Arctic maritime activities will remain unilateral management by each of the coastal states. Thus, the national and local legal and political framework needs to be mapped. In this article we will explore and explain how aqua/-mariculture is governed in the United States (Alaska) and Norway (North Norway). This will be done by examining how parameters for blue economic projects are defined and determined at the international, regional, national and local governance level. Thus, our article will illustrate the complexity behind the blue economy. There is no such thing as one blue economy and no such thing as one Arctic, but it is still possible to find common ground and avenues for knowledge and best practice exchange. By this we will bring the academic and political discussions about the blue economy on the right track.